An expressed sequence tag analysis of the intertidal brown seaweeds Fucus serratus (L.) and F. vesiculosus (L.) (Heterokontophyta, Phaeophyceae) in response to abiotic stressors - Pearson, G. A. (2014)
In order to aid gene discovery and uncover genes responding to abiotic stressors in stress-tolerant brown algae of the genus Fucus, expressed sequence tags (ESTs) were studied in two species, Fucus serratus and Fucus vesiculosus. Clustering of over 12,000 ESTs from three libraries for heat shock/recovery and desiccation/rehydration resulted in identification of 2,503, 1,290, and 2,409 unigenes from heat-shocked F. serratus, desiccated F. serratus, and desiccated F. vesiculosus, respectively. Low overall annotation rates (18–31%) were strongly associated with the presence of long 3′ untranslated regions in Fucus transcripts, as shown by analyses of predicted protein-coding sequence in annotated and nonannotated tentative consensus sequences. Posttranslational modification genes were overrepresented in the heat shock/recovery library, including many chaperones, the most abundant of which were a family of small heat shock protein transcripts, Hsp90 and Hsp70 members. Transcripts of LI818-like light-harvesting genes implicated in photoprotection were also expressed during heat shock in high light. The expression of several heat-shock-responsive genes was confirmed by quantitative reverse transcription polymerase chain reaction. However, candidate genes were notably absent from both desiccation/rehydration libraries, while the responses of the two species to desiccation were divergent, perhaps reflecting the species-specific physiological differences in stress tolerance previously established. Desiccation-tolerant F. vesiculosus overexpressed at least 17 ribosomal protein genes and two ubiquitinribosomal protein fusion genes, suggesting that ribosome function and/or biogenesis are important during cycles of rapid desiccation and rehydration in the intertidal zone and possibly indicate parallels with other poikilohydric organisms such as desiccation-tolerant bryophytes.